New leafminers on Senegalia mellifera (formerly Acacia mellifera, Fabaceae) in Kenya (Lepidoptera: Nepticulidae & Cemiostomidae) are some of Africa’s smallest moths - Nieukerken, Erik J. Van; Agassiz, David J. L. (Zootaxa, 2026)
Two new species of leafminers, occurring on Senegalia mellifera (Vahl) Seigler & Ebinger in Kenya, are described: Acalyptris melliferae sp. nov. in Nepticulidae and Leucoptera aurantia sp. nov. in Cemiostomidae. Both were found in the Rift valley, near Lake Bogoria. These species represent the first known leafminers on the African ‘Acacia’ genus Senegalia. We also provide arguments from phylogenetic studies to consider Cemiostomidae as a separate family, rather than a subfamily in Lyonetiidae. A checklist of African species of Cemiostomidae is appended, the genera Crobylophora Meyrick, 1880 and Microthauma Walsingham, 1891 are synonymised with Leucoptera Hübner, 1825 and the following new combinations are proposed: Leucoptera byssinodes (Meyrick, 1914) comb. nov., L. speciosa (Ghesquière, 1940) comb. nov., and L. xanthochyta (Meyrick, 1918) comb. nov. from Crobylophora and L. metallifera (Walsingham, 1891) comb. nov. from Microthauma.